Biochemical analysis of soft tissue infectious fluids and its diagnostic value in necrotizing soft tissue infections: a 5-year cohort study - Wu, Kai-Hsiang; Wu, Po-Han; Wang, Hung-Sheng; Shiau, Hsiu-Mei; Hsu, Yung-Sung; Lee, Chih-Yi; Lin, Yin-Ting; Hsiao, Cheng-Ting; Lin, Leng-Chieh; Chang, Chia-Peng; Chang, Pey-Jium (Critical care (London, England), 2024)
Necrotizing soft tissue infections (NSTI) are rapidly progressing and life-threatening conditions that require prompt diagnosis. However, differentiating NSTI from other non-necrotizing skin and soft tissue infections (SSTIs) remains challenging. We aimed to evaluate the diagnostic value of the biochemical analysis of soft tissue infectious fluid in distinguishing NSTIs from non-necrotizing SSTIs. This cohort study prospectively enrolled adult patients between May 2023 and April 2024, and retrospectively included patients from April 2019 to April 2023. Patients with a clinical suspicion of NSTI in the limbs who underwent successful ultrasound-guided aspiration to obtain soft tissue infectious fluid for biochemical analysis were evaluated and classified into the NSTI and non-necrotizing SSTI groups based on their final discharge diagnosis. Common extravascular body fluid (EBF) criteria were applied. Of the 72 patients who met the inclusion criteria, 10 patients with abscesses identified via ultrasound-guided aspiration were excluded. Based on discharge diagnoses, 39 and 23 patients were classified into the NSTI and non-necrotizing SSTI groups, respectively. Biochemical analysis revealed significantly higher albumin, lactate, lactate dehydrogenase (LDH), and total protein levels in the NSTI group than in the non-necrotizing SSTI group, and the NSTI group had significantly lower glucose levels and pH in soft tissue fluids. In the biochemical analysis, LDH demonstrated outstanding discrimination (area under the curve (AUC) = 0.955; p < 0.001) among the biochemical markers. Albumin (AUC = 0.884; p < 0.001), lactate (AUC = 0.891; p < 0.001), and total protein (AUC = 0.883; p < 0.001) levels also showed excellent discrimination. Glucose level (AUC = 0.774; p < 0.001) and pH (AUC = 0.780; p < 0.001) showed acceptable discrimination. When the EBF criteria were evaluated, the total scores of Light's criteria (AUC = 0.925; p < 0.001), fluid-to-serum LDH ratio (AUC = 0.929; p < 0.001), and fluid-to-serum total protein ratio (AUC = 0.927; p < 0.001) demonstrated outstanding discrimination. Biochemical analysis and EBF criteria demonstrated diagnostic performances ranging from acceptable to outstanding for NSTI when analyzing soft tissue infectious fluid. These findings provide valuable diagnostic insights into the recognition of NSTI. Further research is required to validate these findings.